Akuntabilitas, Transparansi, Partisipasi Masyarakat dan Pengelolaan Alokasi Dana Desa Untuk Meningkatkan Good Village Governace - Rijal, Moh Syamsul; Handajani, Lilik; Sakti, Dwi Putra Buana (E-Jurnal Akuntansi, 2021)
This study aims to analyze the effect of Accountability, Transparency and Community Participation on the management of Village Fund Allocation (ADD) to improve Good Village Governance (GVG) in West Lombok. The sample of respondents was determined by non-probability sampling, namely purposive sampling. The number of respondents was 108 people who served as Village Head, Village Secretary, Village Treasurer, and Community. Data collection is done by questionnaire. The analysis technique is done by using multiple linear regression analysis model. The results of the accountability research have a positive and significant effect on the management of village fund allocations, as well as transparency has a positive and significant effect on the management of village fund allocations. In contrast, the results of community participation have a positive and insignificant effect on the management of village fund allocations. Practical implications of the research results for village government officials and village heads in West Lombok Regency for the creation of a healthy village fund allocation management. In addition, the formation of an independent village by increasing the village's original income, budget transparency, accountability and transparency. Keywords : Accountability, Transparency, Community Participation, Management Of Village Fund Allocation.